The effect of ozone water disinfection on color stability of nanoparticles reinforced maxillofacial silicones - Suji Daivasigamani; Ahila Singaravel Chidambaranathan; Muthukumar Balasubramanian (European Oral Research)
Purpose: The aim of this study is to evaluate and compare the color stability of nanoparticles reinforced maxillofacial silicone after disinfection with neutral soap, 4% chlorhexidine, and ozone water. Materials and Methods: According to ISO 4823, a metal die was fabricated, and 96 samples were created using Room Temperature Vulcanizing silicone (RTV), Heat Temperature Vulcanizing silicone (HTV), and 3% silicone dioxide nanoparticlereinforced RTV and HTV silicones. The samples were disinfected using neutral soap, 4% chlorhexidine, and ozone water for 10 minutes, three times a day, for 60 days. The samples were divided into four groups: Group 1 (RTV), Group 2 (3% SiO2 nanoparticle-reinforced RTV), Group 3 (HTV), and Group 4 (3% SiO2 nanoparticlereinforced HTV). The color stability of the maxillofacial silicones was evaluated before and after disinfection using a UV spectrophotometer. The obtained color stability values were statistically analyzed using two-way ANOVA and Tukey’s HSD test. Values were considered significant when p < 0.05. Results: The 3% SiO2 nanoparticle-reinforced HTV silicone showed better color stability compared to HTV and RTV silicones, with the least difference observed in the 3% SiO2 nanoparticle-reinforced RTV. Conclusion: Ozone water caused the least change in the color of maxillofacial silicone compared to other disinfectant solutions.